PEMBERDAYAAN MASYARAKAT MELALUI GERAKAN PENGHIJAUAN SEBAGAI UPAYA PENINGKATAN EKONOMI KERAKYATAN PADA SEKTOR PARIWISATA DI DESA COGREG - Wahdiniawati, Siti Annisa; Purnama, Giri; Apriani, Ari; Jumanto, Jumanto (Andhara, 2022)
The resolution of environmental problems can be used as income for the community in Cogreg Village if it is managed properly, such as by creating a typical fruit garden in Cogreg Village such as rambutan, harp, and durian. Because seeing the land around Cogreg Village is fertile land and there are also some people who work as farmers too. By making fruit gardens, at least not just reforestation and environmental problems that are solved, but creating an attraction as a tourist attraction in the Gunung Panjang area, Cogreg Village and this is able to improve the economy of the community from the garden, even if visitors to this garden are felt it will invite MSME actors in Cogreg Village to develop the orchard. Keywords: Karang Taruna, Greening, Village Tourism, Community Economy